2017
DOI: 10.5430/cns.v6n1p76
|View full text |Cite
|
Sign up to set email alerts
|

The professional journey of Saudi nurse graduates: A lived experience

Abstract: Objective: To illuminate the lived experience of Saudi Nurse graduates during their early years in the workplace as professional nurses encompassing their experiences from being nurse students, preparations to become registered nurses, their struggles from being a student to a professional nurse, their cultural competence towards colleagues and patients in their new workplace, their impression of Nursing as a profession and other challenges they faced in especially on language and communication with their pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“… Alboliteeh, Magarey, and Wiechula (2018) reported language barriers as a stressor for Saudi NGNs with English as a second language. Poor language skills affected professional communication and provision of nursing care and negatively impacted on opportunities for learning and advancement.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“… Alboliteeh, Magarey, and Wiechula (2018) reported language barriers as a stressor for Saudi NGNs with English as a second language. Poor language skills affected professional communication and provision of nursing care and negatively impacted on opportunities for learning and advancement.…”
Section: Introductionmentioning
confidence: 99%
“…A study of NGNs by Clark and Springer (2012) found that welcoming staff make NGNs feel like they matter, fit in and integrate with the team, consistent with the findings in Middle Eastern literature. In the Kingdom of Saudi Arabia (KSA), NGNs described lack of acceptance, not being welcomed into the workplace, being ignored, and feelings of isolation ( Alboliteeh, Magarey and Wiechula, 2017 ). Omani NGNs reported expatriate nurses formed cliques resulting in poor collegial relationships, suggesting that ‘Omanisation’ generated a perceived threat to job security for expatriates creating tension and repudiation ( Al Awaisi, Cooke and Pryjmachuk, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations